Precious blood - Hayes, Jonathan, 1960- (Harper, 2007)
Reluctantly assisting in the investigation into the murder of a young student, former forensic pathologist Edward Jenner realizes that a serial killer is at work and incites the wrath of his former boss and nemesis in order to pursue his suspicions.